Pengaruh Solvabilitas terhadap Profitabilitas (Studi pada Perusahaan Asuransi Kerugian yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2018) - Muthia Nur Soniati; Ruhadi Ruhadi; Mochamad Edman Syarief (Indonesian Journal of Economics and Management, 2020)
Insurance Company is developing, proved with the amount of insurance companies now, because companies need to minimalize their risk There were several insurance companies warned by Financial Services Authority. This research has purpose to uncover the impact of Risk Based Capital to Return On Asset.The independent variable is RBC and dependent variable is ROA. The methode is explanatory and quantitative methode with secondary data which is annual financial reports period 2013 – 2018 in insurance companies listed on Indonesia Stock Exchangd that dertermined 5 companies as sample.The statistic are classic assumption test, simple linear regretion, coefficient of determination, and hypothesis test with SPSS version 23. The result by t test showed that Risk Based Capital has positive and significant influence on the Return On Asse. Where the change in Risk Based Capital can explain the change in Return On Asset by 44.9% while the rest is influenced by other factors.